2007
DOI: 10.1111/j.1440-1746.2007.05059.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose intravenous pantoprazole for optimal inhibition of gastric acid in Korean patients

Abstract: A 40 mg b.i.d. dose of pantoprazole is sufficient to maintain pH > 6.0 in Korean patients, except for patients with extensive metabolizing CYP2C19 genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
(40 reference statements)
3
16
0
Order By: Relevance
“…Thus, in our study, patients in the intermittent pantoprazole infusion group received a 2.5 times less daily pantoprazole dose than the continuous infusion group. A Korean study has shown that a low dose (40 mg twice daily) of pantoprazole can maintain an intragastric pH of >6 [16]. In our study, intermittent and continuous pantoprazole infusion treatment had a similar effect on reducing rebleeding, the necessity for rescue therapy, duration of hospital stay and need for blood transfusion.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Thus, in our study, patients in the intermittent pantoprazole infusion group received a 2.5 times less daily pantoprazole dose than the continuous infusion group. A Korean study has shown that a low dose (40 mg twice daily) of pantoprazole can maintain an intragastric pH of >6 [16]. In our study, intermittent and continuous pantoprazole infusion treatment had a similar effect on reducing rebleeding, the necessity for rescue therapy, duration of hospital stay and need for blood transfusion.…”
Section: Discussionsupporting
confidence: 57%
“…Also, the required dose of PPIs may differ according to ethnic groups to achieve an optimal level of acid suppression in bleeding peptic ulcers [24]. It has been speculated that diverse responses to PPIs may be due to a smaller parietal cell mass and more frequent CYP2C19 polymorphism in Asians in comparison to Caucasians [16, 25]. A systematic review and meta-analysis has enhanced the efficacy of PPI therapy for peptic ulcer bleeding in Asia – a post-hoc analysis from the Cochrane Collaboration [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expected that H. pylori-positive patients would have a more severe degree of chronic atrophic gastritis and/or intestinal metaplasia, and the reduction of parietal cell mass caused by these seems to be one reason for these differences. However, this study did not measure the degree of changes in mucosa through Contrary to our expectations, there was no difference in pH according to CYP2C19 genotyping, which confirms previous reports that significant differences are only found at 40 mg per day (20). Our study reaffirmed that these differences are not found at 80 mg.…”
Section: Discussionsupporting
confidence: 77%
“…Rapid ulcer healing through clot stabilization at an elevated intragastric pH is required. Inhibition of gastric acid to maintain a neutral pH could stabilize blood clots and prevent recurrent bleeding [17,18], because the blood coagulation system and platelet aggregation are sensitive to changes in intragastric pH. PPI and H 2 RA are classical acid-suppressing agents, and PPI is no doubt the stronger acid inhibitor for the treatment of gastric ulcer.…”
Section: Discussionmentioning
confidence: 99%